Edukasi Hipertensi dan Pemberian Informasi Obat di Kampung Biru, Banjarmasin, Indonesia: Hypertension Education and Provision of Drug Information in Kampung Biru Banjarmasin, Indonesia - Miranti, Rizka Mulya; Syah, Dhafina Salsabila; Cholisoh, Zakky; Setiawan, Abdul Aziz; Fauzia, Husna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Hypertension poses a serious health challenge in South Kalimantan (prevalence: 30.4%), with low treatment adherence stemming from limited public understanding. This community service initiative aimed to enhance hypertension literacy and medication adherence through education and Drug Information Provision (PIO) in Kampung Biru, Banjarmasin. Methods included health screenings, physician consultations, disease-specific education, drug dispensing with PIO by pharmacists, and knowledge evaluation (pre-test/post-test). Among 58 participants (47 female, 11 male; aged 21–73 years), 25 were diagnosed with hypertension. At the same time, 35 participants showed improved knowledge (average score increase: 0.88 points), 11 experienced declines due to age-related factors and fatigue. Satisfaction surveys indicated 98.27% approval. The program effectively raised community awareness and warrants sustainable implementation with more inclusive approaches.